Ḍākṭar ʻAbdulmuʼīd aur Pākistān lāʼibreriyanship - Nasīm Fā̤timah, 1947-; Ṣamdānī, Raʼīs Aḥmad (Lāʼibrerī Promoshan Biyūro : Milne ke pate, Rāʼil Buk Kampanī, 1981)
Collection of articles on the life and career of Dr. Abdul Moid, a well-known librarian of Pakistan; published on the occasion of silver jubilee celebrations of the Dept. of Library Science, University of Karachi.